REALISM AND THE VICTORIAN ERA: THE GOLDEN AGE OF THE BRITISH NOVEL - Zahro Qodirova Zafarovna (Bright Mind Publishing, 2025)
Realism, which emerged in France in the mid-19th century as a reaction to Romanticism, sought to depict life as it truly was. In England, this movement overlapped with the Victorian era, a period marked by industrial progress, empire expansion, and the flourishing of the novel as the dominant literary form. Writers like Charles Dickens, the Brontë sisters, George Eliot, and Alfred Tennyson shaped this “Golden Age of the British Novel,” combining social critique, realism, and elements of Romantic tradition. The era also saw the rise of children’s literature, reflecting broader cultural and educational changes.
Keywords: Realism, Victorian era, romanticism, novel.